Nuclear magnetic relaxation for the spin-degenerate Anderson model - Whitaker, M. A. [UNESP]; Oliveira, L. N. (Elsevier B.V., 1991)
A renormalization-group calculation of the temperature-dependent nuclear spin relaxation rate for a magnetic impurity in a metallic host is reported. The calculation follows a simplified procedure, which produces accurate rates in the low-temperature Fermi-liquid regime, although yielding only qualitatively reliable results at higher temperatures. In all cases considered, as the temperature T diminishes, the rates peak before decaying linearly to zero in the Fermi-liquid range. For T → 0, the results agree very well with Shiba's expression relating the low-temperature coefficient of the relaxation rate to the squared zero-temperature susceptibility. In the Kondo limit, the enhanced susceptibility associated with the Kondo resonance produces a very sharp peak in the relaxation rate near the Kondo temperature. © 1991.
Keywords: Metals and Alloys; Nuclear Magnetic Resonance; Relaxation Processes; Anderson Model; Kondo Temperature; Magnetic Materials